2012
DOI: 10.1094/pdis-12-11-1036-fe
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Detection ofPhytophthora: Reviewing Our Progress, Identifying Our Needs

Abstract: With the increased attention given to the genus Phytophthora in the last decade in response to the ecological and economic impact of several invasive species (such as P. ramorum, P. kernoviae, and P. alni), there has been a significant increase in the number of described species. In part, this is due to the extensive surveys in historically underexplored ecosystems (e.g., forest and stream ecosystems) undertaken to determine the spread of invasive species and the involvement of Phytophthora species in forest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
0
37

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(198 citation statements)
references
References 243 publications
5
147
0
37
Order By: Relevance
“…Clade 3 contains four homothallic species; all produce semipapillate and caducous sporangia (Kroon et al, 2012;Martin et al, 2012). All four clade-5 species are homothallic and produce papillate and non-caducous sporangia (Kroon et al, 2012;Martin et al, 2012;Weir et al, 2015). Previous studies have suggested that morphological features, especially papillation, are mostly consistent within individual clades or subclades (Kroon et al, 2012;Martin et al, 2012;Yang, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Clade 3 contains four homothallic species; all produce semipapillate and caducous sporangia (Kroon et al, 2012;Martin et al, 2012). All four clade-5 species are homothallic and produce papillate and non-caducous sporangia (Kroon et al, 2012;Martin et al, 2012;Weir et al, 2015). Previous studies have suggested that morphological features, especially papillation, are mostly consistent within individual clades or subclades (Kroon et al, 2012;Martin et al, 2012;Yang, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Even with the addition of P. intercalaris, Phytophthora clade 10 now includes only five formal species. The two other clades that contain fewer species are clades 3 and 5 (Kroon et al, 2012;Martin et al, 2012;Weir et al, 2015). Clade 3 contains four homothallic species; all produce semipapillate and caducous sporangia (Kroon et al, 2012;Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this time an increasing number of damaging species have been described in various ecosystems. For example, P. ramorum, P. pinifolia and P. kernoviae are notable for the economic and environmental damage they have caused in natural ecosystems and nursery production (Brasier et al 2005, Brasier and Webber 2010, Duran et al 2008, Hansen et al 2012, Martin et al 2012. Several new species also have been found during surveys targeting the quarantine pathogens above (Ersek andRibeiro 2010, Kroon et al 2012).…”
mentioning
confidence: 99%